Synthesis of Acyl Hydrazides from Carboxamides and Hydrazine Hydrate Under Metal-Free Conditions at Room Temperature - Singh S.; Kandasamy J. (My University, 2025)
Synthesis of acyl hydrazides from amides has been achieved at room temperature through N-activation reactions. A wide spectrum of functionalized primary and secondary amides was initially converted into N-Boc, N-nitroso and N-tosyl amides and subjected to transamidation with hydrazine hydrate to obtain the desired acyl hydrazides in 76–94% yields. Broad substrate scope, shorter reaction time and mild reaction conditions are the merits of the developed methodology. © 2023 Wiley-VCH GmbH.